THE EFFECT OF DIGITAL SERVICE QUALITY AND ISLAMIC BRANDING ON CUSTOMER LOYALTY OF BYOND BY BSI USERS - Zahrotul Aini, Dewi; Hakim, Lukmanul (Jurnal Dinamika Ekonomi Syariah, 2026)
This study examines the determinants of customer loyalty in Islamic digital banking, focusing on the roles of digital service quality and Islamic branding in the context of BYOND by BSI users in Pamekasan Regency. Using a quantitative explanatory approach, data were collected from 100 active users through structured questionnaires and analyzed using multiple linear regression. The findings reveal that digital service quality significantly enhances customer loyalty through reliable systems, ease of use, responsiveness, and security. Islamic branding also demonstrates a positive and significant influence, reflecting the importance of Sharia compliance and the integration of religious values in strengthening long-term customer commitment. Moreover, both variables simultaneously exert a substantial effect on loyalty, indicating a synergistic relationship between technological excellence and value-based branding. These results suggest that sustainable loyalty in Islamic digital banking is achieved not only through superior digital performance but also through authentic alignment with Islamic principles, offering strategic implications for Islamic financial institutions in regional markets.